Metamorphic evolution of relict eclogite-facies rocks in the Paleoproterozoic Nagssugtoqidian Orogen, South-East Greenland - Müller, Sascha (2018)
The Nagssugtoqidian Orogen in the Tasiilaq region of South-East Greenland, is a roughly southeast-northwesttrending, ~200 km wide Paleoproterozoic collisional orogen. It predominantly consists of a variety of Archean and Paleoproterozoic rocks, which were variably affected by several stages of deformation and metamorphism. The orogen has been subdivided into three different terranes. From north to south, these are the medium-pressure granulite-facies Schweizerland Terrane, the mainly high-pressure amphibolite-facies Kuummiut Terrane and the low-pressure amphibolite-facies Isertoq Terrane with the calc-alkaline Ammassalik Intrusive Complex. In the Kuummiut Terrane, variably retrogressed high-pressure mineral assemblages are preserved within mafic dykes, as well as boudins and boudinaged layers of mafic to ultramafic supracrustal rock in TTG gneiss. These mineralassemblages had previously not been investigated in much detail, but may provide important insight into the conditions of subduction, metamorphism and exhumation in the Paleoproterozoic, an era from which the geothermal regimes and nature of plate-tectonic processes are not well understood and high-pressure rocks are scarce. Within the framework of a larger expedition program to South-East Greenland, this thesis investigated the mineral textural evolution, PT-path and geochronology of variably retrogressed eclogite-facies rocks of the Kuummiut Terrane, via detailed petrological and mineral textural analysis, bulk-rock and mineral chemistry, conventional geothermobarometry, pseudosection modelling, and U-Pb isotopic dating. Well-equilibrated high-pressure and amphibolite-facies mineral assemblages, with only minor replacement textures, were found in garnet-pyroxenite, garnet-amphibolite and garnet-kyanite schist. Retrogressed eclogite, in contrast, is characterized by complex mineral reaction textures and the formation of two chemically and mineralogically distinct domains, leading to domainal equilibration volumes. A clinopyroxene domain is dominated by a ...